SATISFACTION IN CARING FOR OLDER ADULTS WITH ALZHEIMER’S: PERCEPTIONS OF THE FAMILY CAREGIVERS - Fabiana Cristina Vidigal; Roberta Fernanda Rogonni Ferrari; Daysi Mara Murio Ribeiro Rodrigues; Sonia Silva Marcon; Vanessa Denardi Antoniassi Baldissera; Lígia Carreira (Cogitare Enfermagem, 2014)
This study aimed to ascertain the conditions of satisfaction of family caregivers for older adults with Alzheimer’s Disease in the municipality of Umuarama in the Brazilian state of Paraná (PR). It is a qualitative, descriptive and exploratory study, undertaken with eight family caregivers. The data were collected in the period July – September 2013, through semistructured interviews held in the caregivers’ homes and later subjected to analysis, from which four categories emerged: The experience with the care allows the development of skills; The provision of well-being to the older adult affords satisfaction to the family caregiver; Religiosity promotes satisfaction in caring; and Demonstrating love and gratitude through the care promotes the satisfaction of the family caregiver. The results indicated that satisfaction also exists in the act of caring, demystifying the imaginary that this activity is permeated only by dissatisfaction and overload.